Frailty and Associated Outcomes and Resource Utilization Among Older ICU Patients With Suspected Infection. Issue 8 (August 2019) - Fernando, Shannon M.; McIsaac, Daniel I.; Perry, Jeffrey J.; Rochwerg, Bram; Bagshaw, Sean M.; Thavorn, Kednapa; Seely, Andrew J. E.; Forster, Alan J.; Fiest, Kirsten M.; Dave, Chintan; Tran, Alexandre; Reardon, Peter M.; et al.
Abstract : Objectives: Suspected infection and sepsis are common conditions seen among older ICU patients. Frailty has prognostic importance among critically ill patients, but its impact on outcomes and resource utilization in older patients with suspected infection is unknown. We sought to evaluate the association between patient frailty (defined as a Clinical Frailty Scale ≥ 5) and outcomes of critically ill patients with suspected infection. We also evaluated the association between frailty and the quick Sequential Organ Failure Assessment score. Design: Analysis of a prospectively collected registry. Setting: Two hospitals within a single tertiary care level hospital system between 2011 and 2016. Patients: We analyzed 1, 510 patients 65 years old or older (at the time of ICU admission) and with suspected infection at the time of ICU admission. Of these, 507 (33.6%) were categorized as "frail" (Clinical Frailty Scale ≥ 5). Interventions: None. Measurements and Main Results: The primary outcome was in-hospital mortality. A total of 558 patients (37.0%) died in-hospital. Frailty was associated with increased risk of in-hospital death (adjusted odds ratio, 1.81 [95% CIs, 1.34–2.49]). Frailty was also associated with higher likelihood of discharge to long-term care (adjusted odds ratio, 2.06 [95% CI, 1.50–2.64]) and higher likelihood of readmission within 30 days (adjusted odds ratio, 1.83 [95% CI, 1.38–2.34]). Frail patients had increased ICU resource utilization and total costs. The combination of frailty and quick Sequential Organ Failure Assessment greater than or equal to 2 further increased the risk of death (adjusted odds ratio, 7.54 [95% CI, 5.82–9.90]). Conclusions: The presence of frailty among older ICU patients with suspected infection is associated with increased mortality, discharge to long-term care, hospital readmission, resource utilization, and costs. This work highlights the importance of clinical frailty in risk stratification of older ICU patients with suspected infection. Abstract : Supplemental Digital Content is available in the text.